2019
DOI: 10.3390/rs11111347
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Urban Sensible Heat Flux from Remotely Sensed Surface Temperature: Effects of Surface Structure

Abstract: Sensible heat exchange has important consequences for urban meteorology and related applications. Directional radiometric surface temperatures of urban canopies observed by remote sensing platforms have the potential to inform estimations of urban sensible heat flux. An imaging radiometer viewing the surface from nadir cannot capture the complete urban surface temperature, which is defined as the mean surface temperature over all urban facets in three dimensions, which includes building wall surface temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This means that a roof top facet may not affect the urban canopy layer air temperature near the ground, while the wall or road or other near ground facets would do so. Thus, the complete surface temperature is useful to study urban climate since it provides the information required for urban climate research, for example, to estimate sensible heat flux (Voogt and Grimmond, 2000; Yang et al ., 2019) and other heat flux densities.…”
Section: Introductionmentioning
confidence: 99%
“…This means that a roof top facet may not affect the urban canopy layer air temperature near the ground, while the wall or road or other near ground facets would do so. Thus, the complete surface temperature is useful to study urban climate since it provides the information required for urban climate research, for example, to estimate sensible heat flux (Voogt and Grimmond, 2000; Yang et al ., 2019) and other heat flux densities.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the geometric data were not available in other areas to replicate our analysis. We have studied the surface heat fluxes over Hong Kong earlier (Wong et al, 2015;Yang et al, 2019;Yang et al, 2016). Results from these previous studies showed that the method applied to estimate sensible heat flux in this study is appropriate to estimate sensible heat flux in Hong Kong urban areas (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…6 is also widely used to estimate the sensible heat flux in urban areas (Voogt and Grimmond, 2000;Xu et al, 2008). This parameterization method has been used in previous studies of sensible heat flux estimation in Hong Kong with reasonable results (Wong et al, 2015;Yang et al, 2019;Yang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…ENVI-met, a micro-scale 3D computational fluid dynamics (CFD) model ( Wang and Akbari, 2016 ; Chatterjee et al, 2019 ; Pigliautile et al, 2020 ) and Weather Research Forecast (WRF) coupled with the single- or multi-layer urban canopy layer model (UC) ( Imran et al, 2018 ; Jandaghian and Akbari, 2018 etc.) are the two most common modelling tools ( Table 3 ), followed by others such as Ecosystem Service Model ( Venter et al, 2020 ), Open Studio and EnergyPlus ( Yang et al, 2018a ), Town Energy Balance (TEB) coupled with the Interaction Soil Biosphere Atmosphere (ISBA) model ( Daniel et al, 2018 ), Surface Energy Balance ( Mariani et al, 2016 ), SURFEX ( Broadbent et al, 2018 ), and TUF-3D ( Yang et al, 2019 ). ENVI-met is commonly used to simulate air-surface-plant-interactions in urban environments ( Crank et al, 2018 ; Tiwary and Kumar, 2014 ).…”
Section: Assessment Framework: Overview Of Modelling Approachesmentioning
confidence: 99%